Developing Picture Storybook in English with Wetlands Theme for Young Learners - Emma Rosana Febriyanti; Fahmi Hidayat (Universitas Muhammadiyah Kalimantan Timur, 2023)
Stories encourage young learners to understand concepts and vocabulary while expanding their background knowledge about their surroundings. Therefore, providing young learners with a variety of storybooks to develop their understanding of their environment is important to be done by considering their interests and the content of the books. Based on this view, this research aimed to design a picture storybook written in English and with a wetlands environment. Simultaneously this research and development (R&D) referred to development procedures by Borg and Gall (2007) that simplified the process to only seven procedures: prelim approach methods data collection, research planning, early product development, expert validation, revision, field testing, and the last is disseminating and implementing the final product. The instruments used to collect data were a questionnaire, an interview with 15 kindergarten teachers on the need analysis stage and field testing stage, and two validation sheets validating the content and design stage. The results from data analysis showed that it is important to name some animals and plants that live specifically in South Kalimantan wetlands as the main characters of the storybook, such as timpakul, haruan, papuyu, bekantan, mangrove trees, and kasturi. Next, the developed picture storybook was feasible to be used as media for introducing English and wetlands since it was proven to be valid, practical, and effective.